Pelatihan Pembuatan Media Pembelajaran Berbasis Google Sites di UPT SMP Negeri 19 Gresik - Muwafiqus Shobri; Qois Rifqi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Teachers are required to take advantage of various learning technologies available in today's classrooms. For this reason, various efforts are needed in the learning process. One of these efforts is the use of Google sites-based learning media which aims to facilitate the teaching and learning process for teachers. Because of the importance of increasing teacher competence and skills in utilizing instructional media to the fullest, it is necessary to have training in the creation and use of Google sites-based learning media for the teacher council. The aim of the training is to broaden horizons and strengthen teacher competency skills in creating and using Google sites as learning media. This training was held on February 16, 2023 at UPT SMP Negeri 19 Gresik which was attended by 15 teachers and was carried out in two stages, namely first delivering material on the concepts and benefits of Google sites as learning media, and the second stage directly practicing creating and operating Google sites as a learning media. instructional Media. This training was carried out using a combination of material presentation methods, hands-on practice and direct debriefing. The results of this training activity, the training participants who were all teachers at UPT SMP Negeri 19 Gresik were able to understand the concepts and benefits of Google sites as well as being able to create and use websites based on Google sites as learning media.